Treatment Adherence as Predictor of Outcome in Concentrated Exposure Treatment for Obsessive-Compulsive Disorder - Tjelle, Kristian; Opstad, Håvard Berg; Solem, Stian; Launes, Gunvor; Hansen, Bjarne; Kvale, Gerd; Hagen, Kristen (Frontiers in Psychiatry, 2021)
Abstract Background: The treatment of choice for obsessive-compulsive disorder (OCD) is exposure and response prevention (EX/RP). Previous studies have demonstrated that treatment adherence predicts treatment outcome for patients with OCD, but there is little knowledge on its role in concentrated exposure treatment for OCD. Method: In the present study, 42 patients received EX/RP treatment using the Bergen 4-day format. Adherence was measured with the Exposure and Response Prevention Adherence Scale (PEAS, rated both by patients and therapists) after the second and third day. Treatment outcome (symptoms of OCD, depression, anxiety, work- and social functioning, and well-being) was assessed at 3-month follow-up. Results: At follow-up, 71.4% were in remission. High adherence was reported (mean score of 6 on a 1-7 scale). The combination of patient- and therapist rated adherence was significantly associated with treatment outcome whilst controlling for age, sex, and pre-treatment scores. Patients with higher degree of adherence reported less symptoms, higher functioning, and more well-being at follow-up. Conclusions: The results of the present study indicated that adherence in concentrated exposure treatment is significantly associated with a wide range of treatment outcomes for OCD.